HUBUNGAN PENGETAHUAN IBU TENTANG GIZI DAN TUMBUH KEMBANG ANAK SERTA STIMULASI PSIKOSOSIAL DENGAN PERKEMBANGAN KOGNITIF ANAK USIA 2-5 TAHUN - Rahmaulina, Novera Dwi; Hastuti, Dwi (Jurnal Ilmu Keluarga dan Konsumen, 2008)
Purpose of this research were (1) to identify family’s and child’s characteristics, (2) to identify mother’s knowledge on nutrition and child’s growth development, mother’s access to information on nutrition and child growth development, psychosocial stimulation, and child’s cognitive development, (3) to analyze relationship between family’s characteristics and mother’s knowledge on nutrition and growth development, (4) to analyze relationship of family’s characteristics, mother knowledge, child’s characteristics and psychosocial stimulation, (5) to analyze relationship between mother’s knowledge, psychosocial stimulation and child’s cognitive development. A cross sectional design was assigned for this research. Population of this research were children aged 2-5 years old that located at Sub capital East Bogor and Kedungbadak were selected by random proportional from 297 children’s to 100 sample which consist of aged 2-3 years old (37 children), 3-4 years old (50 children), and 4-5 years old (33 children). A correlation test of Rank Spearman was applied to test the correlation among variables. Results showed that there were significant and positive relationship among three variables which were family’s characteristics (family’s income and mother’s education) and mother’s knowledge. Meanwhile, mother’s and father’s educational attainment and family’s income had a positive and significant correlation with psychosocial stimulation.. The study also found that psychosocial stimulation and mother’s knowledge had a significant and positive relationship with child’s cognitive development.